Theory of asset pricing - Pennacchi, George Gaetano (Boston : Pearson/Addison-Wesley, 2008)
"Theory of Asset Pricing unifies the central tenets and techniques of asset valuation by striking a balance between fundamental theories and cutting-edge research. Pennacchi offers the reader a well-rounded introduction to modern asset pricing theory that is presented in an intuitive, user-friendly manner."--BOOK JACKET.
Pt. I. Single-period portfolio choice and asset pricing -- 1. Expected utility and risk aversion -- 2. Mean-variance analysis -- 3. CAPM, arbitrage, and linear factor models -- 4. Consumption-savings decisions and state pricing -- Pt. II. Multiperiod consumption, portfolio choice, and asset pricing -- 5. A multiperiod discrete-time model of consumption and portfolio choice -- 6. Multiperiod market equilibrium -- Pt. III. Contingent claims pricing -- 7. Basics of derivative pricing -- 8. Essentials of diffusion processes and Ito's Lemma -- 9. Dynamic hedging and PDE valuation -- 10. Arbitrage, martingales, and pricing kernels -- 11. Mixing diffusion and jump processes -- Pt. IV. Asset pricing in continuous time -- 12. Continuous-time consumption and portfolio choice -- 13. Equilibrium asset returns -- 14. Time-inseparable utility -- Pt. V. Additional topics in asset pricing -- 15. Behavioral finance and asset pricing -- 16. Asset pricing with differential information -- 17. Models of the term structure of interest rates -- 18. Models of default risk.
Includes bibliographical references (p. 415-431) and index.
Keywords: Capital assets pricing model; Securities